Michał Römer w Wilnie 1940 roku - Maaksimamaitis, Mindaaugaas (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
1940 year was very significant in the life of Römer, because he abandoned Kaunas for Vilnius. In the same time the great lawyer ended his activity as arector of Vytautas Magnus University in Kaunas what, together with the effect of migration, limited in many areas the possibility of effective collaboration with Lithuanian government.In ancient Gediminas capital Römer not only worked at the University, but also made many efforts for coexistence Poles and Lithuanians. But after six months, after the unification of Baltic Republics with USSR, the situation seriously changed. Römer as the “socially alienated” and “politically unsafe” was not avaluable person in the eyes of Soviet clerks, so he went to the “internal emigration”, but constantly taught at the University as the lecturer of objective science.
Keywords: Romeris Mykolas (1880-1945); Vilnius